The Influence of Family Environment and Attitudes of Buddhist Sunday School Teachers on the Character of Generation Z in the Globalization Era in Makassar - Karunia Dewi Pudjohadi; Ida Bagus Dharmika; Mujiyanto Mujiyanto (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Globalization and technological advancements have influenced the character of Generation Z, who grew up exposed to foreign cultures through social media. The values that Generation Z receive often conflict with local culture and religious teachings, including Buddhism. In this regard, families and Buddhist Sunday School (SMB) teachers play an important role as moral and spiritual educators. However, weak family communication and teachers' inconsistency in conveying religious values pose obstacles. Initial studies at several monasteries in Makassar indicate that their roles are still not optimal. This study aims to examine the influence of the family environment and SMB teachers' attitudes on the character of Generation Z in the context of Buddhist religious education in the era of globalization. This study uses a quantitative method with a regression approach to analyze the influence of the family environment and SMB teachers' attitudes on the character of Generation Z. This study concludes that the family environment and the attitudes of Buddhist Sunday School teachers have a positive and significant influence on the character of Generation Z in Makassar, both individually and collectively, with a combined contribution of 26.2%. Character strengthening can be achieved through the active role of families and teachers, as well as synergy between monasteries, schools, and families in educational programs and development based on Buddhist values.